Environmental influences in normal weight women with history of recurrent pregnancy loss (2013)
Aim: The study investigated the possible relationship of luteal phase progesterone, toxic heavy metals and nutrients in normal-weight women with history of recurrent pregnancy loss for adequate management. Study Design: Cross sectional study. Place and Duration of Study: The Obstetrics and Gynaecology Clinic, University College Hospital, Ibadan, Olabisi Onabanjo University Teaching Hospital, Shagamu and State Hospital, Ijebu-Ode; the University of Ibadan and environs between April and September, 2009. Methodology: 90 apparently healthy women with normal weight aged 18-45years with regular and ovulatory cycles of 26-30 days were enrolled. They were 60 women with history of recurrent pregnancy loss (cases) age-matched with 30 women without history of recurrent pregnancy loss (controls). Demographic and anthropometric measurements were done by standard methods. Progesterone was determined by enzyme immunoassay (Immunometrics UK Ltd). Total cholesterol, triglyceride and high density lipoprotein were performed by enzymatic methods (Randox laboratories, USA) while low density lipoprotein was calculated using Friedwald’s formula. Zinc, selenium, chromium, manganese, iron, magnesium, copper, lead, and cadmium were estimated by atomic absorption spectrophotometry while Vitamin E was measured by high performance liquid chromatography. Statistical analysis was done using SPSS version 16.0. Results: Results showed significantly higher levels of triglycerides, cadmium and lead, and significantly lower levels of progesterone, iron, copper, magnesium, chromium, selenium and vitamin E in cases compared with controls (p<0.013). Conclusion: Oxidative stress mechanisms in normal-weight women with history of recurrent pregnancy loss were implicated. Healthcare policies should focus on pollution reduction and increase awareness on healthy diet for optimal periconceptional micronutrient requirements.